The rise of a new corporate form. - Moore, James F. (Washington Quarterly)
The writer discusses the emergence of a new form of corporate structure and organization. Business leaders today must learn to see their business not as hierarchical structures but as participants in a world of complex evolving systems. The new strategic paradigm involves asserting leadership rather than control over groups of individuals and organizations; recognizing and utilizing the intelligence of colleagues and working in tandem to develop new innovation; and working toward a better future rather than merely resting upon the achievements of the past. Innovation, in the sense of meeting or establishing new customer needs by bringing together hitherto unmatched or less-well-integrated resources, is the only true sustainable advantage in today's business environment. For a company to make any real innovative advances, it requires complementary adaptations by other organizations.